Recursive Curve Modeling of I-V Curve for A-Si Photovoltaic Cells - FU Zhen; SHI Nan; ZHU Xianhui; LIU Zhongwu (Journal of Harbin University of Science and Technology)
To explore an accurate and simple method for fitting the I-V characteristics of photovoltaic cells, two recursive curves were used to characterize the output characteristics of different types of photovoltaic cells. Taking a-Si batteries as an example, the short-circuit current point is taken as the first vertex of the first recursive curve control polygon, and the maximum power point is taken as the third vertex. Similarly, the maximum power point is taken as the first vertex of the second recursive curve control polygon, and the open circuit voltage point is taken as the third vertex. The positions of the second vertex of two control polygons on a straight line parallel to the short-circuit current and open-circuit voltage points are determined, and passing through the maximum power point. Furthermore, the variation law of the second vertex position of the control polygon with the manufacturer ′ s given fill factor was discovered when the error was the smallest, and a fitting method for I-V characteristics of a-Si batteries was constructed based on this variation law. Then, according to the above method, the variation pattern of the second vertex position of other types of photovoltaic cell control polygons with the fill factor given by the manufacturer was discovered. Finally, recursive modeling was conducted on the I-V characteristics of five types of batteries, and the accuracy and simplicity of the proposed modeling method were systematically demonstrated by comparing it with the existing four modeling methods in terms of average relative error, absolute error, and root mean square error.